Petrolisthes extremus o Petrolisthes coccineus (Decapoda Anomura Porcellanidae), ¿están las dos especies presentes en Isla de Pascua? - Guillermo Guzmán (Revista de Biología Marina y Oceanografía, 2016)
Two morphologically similar species of porcellanid crabs have been cited around Easter Island, Petrolisthes coccineus and P. extremus. New material collected in different locations of the island, only support the presence of P. extremus. The specimens used in the records of P. coccineus in Easter Island are deposited in the Museo Nacional de Historia Natural of Santiago and the Museo de Zoología of the Universidad de Concepción. After checking this material identified as P. coccineus, it was concluded that just one species is found in Easter Island and correspond to P. extremus.